Peran Rumah Detensi Imigrasi Medan Dalam Peningkatan Kapasitas Masyarakat Kota Medan - Sivakkar, Sarsaralos; Anggusti, Martono (Universitas Medan Area, 2023)
This research is about the function of immigration as a facilitator of community welfare development. In the explanation of Law Number 6 of 2011 concerning Immigration (Immigration Law), it is stated that foreigners who are allowed to enter and reside in Indonesia are people who bring benefits to the nation, state, and Indonesian society. The Medan Immigration Detention Center is one of the technical implementation units of the Directorate General of Immigration which carries out immigration functions. This research was conducted for whether the Medan Immigration Detention Center as mandated in the Immigration Law as a temporary shelter for foreigners subject to immigration administrative measures can carry out its immigration function as a facilitator for community welfare development by playing a role in increasing the capacity of the people of Medan city. This research was designed using qualitative research methods with a case study approach. The results of the research prove that the Medan Immigration Detention Center with the My Hobby Is innovative and collaborating with stakeholders can transfer knowledge from the detention center to the Medan city community, in this case, the inmates of the Medan State Women's Detention Center. It was proven that the training carried out together had a role from the Medan Immigration Detention Center